(3cTa GdMPQ Yf CeQ GdNVQs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi ChLOfG HLhOg CeG HYO ajbhd Cf gPg ebGdI ai HjGf MGd GdNVQ ef fSHg hMSHg heG jJYdb Hg ef CeQ hdGjJg hfHhJg s
(3BNQgG (B:s
(3bdJ hgPG eLGRaI ai GdcdGe aef Cjf dg fai gPg GdCTjGA ef GdNVQ Ydjg GdSdGe hdG jbGS Gdedhc HGdMOGOjf aSHMGf ef CbGe GdYHGO ajeG CQGO aGdJSdje CSde hGddg SHMGfg CYde hHeG bOQg hbVGg CMce hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B136) s
Keywords: (3GdeLGejYs